Geomatics correction model for GPS data using RTK-DGPS survey - Hussein, Alaa A.; Mahmood , Faleh H. (Iraqi Journal of Science, 2022)
Determination of the sites of geographical coordinates with high accuracy and in short time is very important in many applications, including: air and sea navigation, and in the uses geodetic surveys. Today, the Global Positioning System (GPS) plays an important role in performing this task. The datum used for GPS positioning is called World Geodetic System 1984 (WGS84). It consists of a three-dimensional Cartesian coordinate system and an associated ellipsoid so that WGS84 positions describe coordinates as latitude, longitude and ellipsoid height (h) coordinates, with respect to the center of mass of the Earth This study develops a mathematical model for geomantic measurement correction for ellipsoidal heights (h) between two different receivers of different accuracies (i.e. high and low). The results are examined using statistical analysis for the accuracy and reliability of the computed positions. The receivers used in this study were, the Topcon HiPer-II and the Garmin eTrex vista. The first receiver use Global Navigation Satellite Systems (GNSS) signals on the L1 and L2 frequencies of both the GPS and GLONASS satellite navigation systems, while the second receiver was the Garmin eTrex vista.